Comparison of commercially available preformed archwires with average natural arch forms - Mughal, Alaina Tariq; Jan, Abdullah; Akhtar, Obaid; Ghaffar, Fareena; Shafique, Hafiza Zobia; Shahid, Rooma (Journal of the Pakistan Medical Association, 2021)
Objective: The research was carried out to compare the dimensions of commercially available preformed archwires with natural arch forms of Pakistani subjects. Methods: An observational study that lasted for 6 months was conducted at AFID, Rawalpindi. Fifty-two maxillary and mandibular dental casts of orthodontically untreated subjects (26 males and 26 females) were evaluated to obtain arch dimensions at the canines and first molar levels with the help of digital Vernier calipers. Bracket-archwire assembly was constructed to accurately measure widths from bracket-slot (BS) points at both the canine and molar levels, in an attempt to mimic clinical archwire-bracket interface. Canine and molar depths were also recorded for accurate estimation of the digitized archwire widths at the aforementioned levels. Results: The archwires evaluated for maxilla were significantly wider at canines (42.16 ±1.84mm, p = 0.000) and first molars (58.45 ± 1.33mm, p = 0.014) compared to the canine and molar dimensions of the dental casts obtained from subjects (37.61 ± 3.75mm, 55.68 ± 4.05mm respectively). For mandible, statistically significant differences were found at the canine level where archwires (34.75 ± 1.66mm, p = 0.000) exhibited greater dimensions than mean intercanine widths (29.33 ± 3.35mm) of the subjects. Conclusion: At present, commercially obtainable preformed archwires are inconsistent with the diverse arch forms manifested in a group of subjects with almost ideal occlusion. Therefore; utilization of these archwires may create unwarranted wider dimensions of the arch form, especially in the intercanine region which can influence post treatment retention, stability and facial esthetics. Continuous..